A Palladium-Catalyzed Three-Component Cross-Coupling of Conjugated Dienes or Terminal Alkenes with Vinyl Triflates and Boronic Acids - Liao, Longyan (2011)
A three-component coupling of vinyl triflates and boronic acids to alkenes catalyzed by palladium is reported. Using 1,3-dienes, selective 1,2-alkene difunctionalization is observed, whereas the use of terminal alkenes results in 1,1-alkene difunctionalization. The reaction outcome is attributed to the formation of stabilized, cationic Pd-π-allyl intermediates to regulate β-hydride elimination.